Gender Differences in Competitiveness and Risk-Taking among Children, Teenagers, and College Students: Evidence from Jeopardy! - Michael Jetter; Jay K. Walker (Institute of Labor Economics (IZA), 2017)
Studying competitiveness and risk-taking among Jeopardy! contestants in the US, this paper analyzes whether and how gender differences emerge with age and by gender of opponent. Our samples contain 186 children (aged 10–12), 310 teenagers (aged 13–17), and 299 undergraduate college students. We measure competitiveness via the likelihood of (i) winning an episode, (ii) responding to a clue (i.e., 'buzzing' in), and (iii) responding correctly to a clue. Risk-taking is assessed via Daily Double wagering decisions. We identify no noticeable gender differences in our competitive measures throughout all three samples, but this result changes when considering risk-taking. Although we identify no gender differences in wagering for children, males begin to wager substantially more as they become teenagers, leading to the emergence of the gender gap. In terms of magnitude, teenage girls wager 7.3 percentage points less of their maximum wager than teenage boys, equivalent to approximately 451. This gap persists for college students, albeit with a somewhat smaller magnitude of 297. Finally, male teenagers and college students wager substantially less when competing against females. In turn, the gender of opponents does not influence female competitive behavior and risk-taking.
Keywords: D81; D91; G41; J16; 330; competitiveness; risk preferences; gender differences; performance under high pressure; gender of opponents